Dynamic Model of Flexible Link Manipulators with Translational and Rotational Joints - Duong, Xuan Bien; Chu, My Anh; Phan, Bui Khoi (Old Journal, 2018)
In this paper, two nonlinear dynamic models of flexible manipulator with translational and rotational joints are formulated based on Finite Element Method (FEM). Dynamic equations of manipulators are derived by using Lagrange equations. The new model TR (Translational-Rotational) is developed based on single flexible link manipulator with only rotational joint. The difference between flexible manipulators which have only rotational joints and others with translational joint is presented in RT model. Dynamic behaviors of flexible manipulators are analyzed through values of joints variable and elastic displacements at the end-effector point. The numerical simulation results are calculated by using MATLAB/SIMULINK toolboxes. The results of this study play an important role in modeling generalized planar flexible two-link robot, in designing the control system and basing on select the suitable structure robot with the same request.